Water conservation techniques in surface irrigation at plantation level - Flores-Gallardo, Hilario; Sifuentes-Ibarra, Ernesto; Flores-Magdaleno Héctor; Ojeda-Bustamante, Waldo; Ramos-García Cristo R. (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the availability of water in arid and semi-arid areas is highly critical. The agricultural sector requires large volumes of water to meet the water requirements of crops. Despite the acquisition of irrigation systems to have an efficient management of water, most of the agricultural areas have inadequate irrigation technology that generates conveyance losses and water distribution. Gravity irrigation at plantation level has a low efficiency in implementation and there is no measurement and irrigation scheduling to meet the demands of the crop in terms of timeliness and efficiency as well. This research was conducted in northern Sinaloa, Mexico during the autumn-winter 2006-2007 season, sowing maize (Zea mays L.) in the Fort Valley Experimental Field (INIFAP) and with a cooperating producer. The water conservation techniques in surface irrigation evaluated were: irrigation in beds, irrigation expenditure reduction, alternate furrow irrigation and conventional irrigation. Alternate furrow technique was the best alternative in terms of irrigation efficiency and performance, getting in the Experimental 13.8 t ha-1 on average, 83.65% efficiency of application and 88.19% uniformity, and producer 11.86 t ha -1 with 79% efficiency of application and 83.42% uniformity.